SUSTAINABLE DEVELOPMENT AND ITS STAGES OF DEVELOPMENT - Nabiyeva Durdona Dilshod qizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides a statistical analysis of the history of sustainable development and its development, the goals and objectives of sustainable development.